Removal of Metal Fixators after Consolidation of Bone Fractures: To Do or Not to Do? (Literature Review) - Kalashnikov, A.V.; Verkhovskyi, O.V.; Kalashnikov, O.V.; Procenko, V.V. (TERRA ORTHOPAEDICA, 2022)
Summary. Removal of metal fixators today is one of the most common surgical interventions in developed countries. According to many European researchers, surgeries performed to remove metal fixators account for almost 30% of all planned surgical interventions and 15% of the total number of surgeries performed in trauma departments. This certainly indicates the great social significance of the problem. An analytical review of the literature has shown that the surgery of removing metal fixators in the consolidation of bone fractures is not a routine procedure; it requires experience and training of the surgeon. The problem of removal of metal fixators in some individual cases and localizations is not completely solved and requires further clinical and experimental studies.